การตรวจสอบบัญชีในระบบคอมพิวเตอร์ - สุชาติ เหลืองสุรสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1974)
The theory and use of electronic Data Processing has developed very rapidly in recent times and shows no sign of receding, coupled with this is the fact that various business concerns have initiated the use of computers to keep financial records and documentation in increasing numbers and show trend of increasing evermore in the future. This is because it is not only large business concerns that adopt electronic data processing systems, medium and small business concerns as well are able to benefit from electronic data processing through the use of small computer models or the use of computer service centers. Furthermore, the introduction of advanced electronic data processing system, such as on-line, real-time and integrated systems, including time-sharing system of computer service centers and the recording of various data on magnetic tape or on magnetic disc, or other devices which are not in a visible state, have made it necessary for auditors to develop new auditing techniques to keep abreast of developments in this field. Since the various aspects of electronic data processing systems, such as the nature of data controls, especially in the area of administrative and procedural controls, especially in the area of administrative and procedural controls, techniques of evaluating internal control, including the method of determining audit trail, which differ from non-electronic data processing system. In researching for this thesis, the writer has made use of information from available text books, from articles and opinions of accountants in various publications, research papers, documents in audit firms, including personal experiences gained directly from the auditing of electronic data processing system. Because this topic has not previously been seriously researched in Thailand, the data which are incorporated into this paper are gleaned from various research papers which have been compiled abroad, including documents and auditing manuals of Coopers & Lybrand, where the writer is presently working and another firm of accountants, where the writer used to work. Both are International Public Accountants who have made use of special auditing techniques developed by their offices abroad, such as in the United States of America and England. At the present time special audit techniques, such as the use of test packs or computer audit programs, are relatively new to Thailand, however they will increase in importance with time and the auditor will no longer be able to avoid the necessity of utilizing the computer in auditing, if the electronic data processing system is developed to the point where the auditing of certain records cannot be performed by manual examination. This approach is now considered unsatisfactory for even the smallest computer based system. The writer believes that this thesis will urge the body concerned with auditing to realize the impact of computers on auditing and turn to develop auditing techniques, and to suggest how the auditor may benefit from the use of computer in auditing rather than regard it as an obstacle. And at the same time, this thesis will serve as a guideline for those who wish to research further on the subject as well.